Does sleep duration, napping, and social jetlag predict hemoglobin A1c among college students with type 1 diabetes mellitus?. (February 2019) - Saylor, Jennifer; Ji, Xiaopeng; Calamaro, Christina J.; Davey, Adam
Abstract: Aims: The first aim examined the relationship between sleep behaviors (duration, napping, and social jetlag) and hemoglobin A1c (HbA1c) among emerging young adults (EYAs) with T1DM between 18 and 25 years old, who are living on a college campus. The second aim characterized the gender differences in glucose management, sleep behaviors, caffeine intake, and nighttime technology. Methods: A cross-sectional study of eligible participants used a convenience sample of eligible participants. Using Research Electronic Data Capture (REDCap), participants completed surveys about diabetes management, caffeine intake, nighttime technology use, and sleep-related behaviors. Data were analyzed using correlation and multiple linear regression to predict HbA1c from sleep behaviors, adjusting for covariates. Results: Participants (N = 76) average years with T1DM was 10.25 ± 5.70. Compared to females, males had a longer sleep duration lower HbA1c levels. HbA1c levels were negatively correlated with weekday sleep (r = −0.24, p = 0.03) and positively correlated with napping (r = 0.34, p = 0.003). After adjusting for covariates, participants who napped had a higher HbA1c level (β = 0.74, p = 0.03) compared with non-nappers. Conclusions: Higher HbA1c levels were found among EYAs with T1DM in college who were nappers and had a longer sleep duration. Modifying sleep behaviors may be an appropriate target to improve glycemic control.